Communication technology practices used by midwives with pregnant women/people in Aotearoa New Zealand to ensure quality maternal and newborn care. (May 2023) - Wakelin, Karen J; McAra-Couper, Judith; Fleming, Tania; Erlam, Gwen D.
Abstract: Introduction: Communication technology such as texting is commonly used for sending appointment reminders and reinforcing health messages. Midwives have identified concerns with privacy of information or information taken out of context within an online format. How this technology is used to ensure quality maternal care within a continuity model of midwifery care is unknown. Aim: To describe midwives' experiences of using communication technology with pregnant women/people in Aotearoa New Zealand. Methods: A mixed methods design was used to collect online survey data from Lead Maternity Carer midwives. Recruitment was through closed midwifery Facebook groups in Aotearoa New Zealand. Survey questions were informed by the Quality Maternal & Newborn Care framework & findings and an integrative literature review. Quantitative data was analysed using descriptive statistics, and qualitative comments analysed using thematic analysis. Findings: 104 midwives responded to the online survey. Phone calls, texting and emails were commonly used by midwives to reinforce health messages and decision making. Communication technology supported, and enhanced relationships midwives develop with their pregnant clients. Texting enhanced documentation of care and enabled midwives to work efficiently. Midwives, however identified concerns when managing expectations around urgent and non-urgent communication. Discussion: Midwives are bound by regulations to ensure they provide safe care to pregnant women/people. Negotiating and understanding expectations around use of communication technology is vitally important to ensure that communications and connections are undertaken in a safe manner.